(untitled) (Fiep Bulletin - online, 2011)
The aim of this study was to evaluate the psychomotor diagnose motor age of pre - school children, and to examine whether regional customs influence the development of the same engine. Participants 138 children of both sexes aged from 4.6 to 6.10 years, 117 were enrolled in the School Urbana located in Manaus, AM, 57 of those were during the mornings (they had no physical education classes) and 60 the morning hours (they had two classes per week of physical education). The other 21 subjects were from the Rural School, located in the Village of Lindenow / Itacoatiara. The instrument was the Scale of Motor Development. The tests were Kinetics Global (Gk), Fine Motor (FM), Equilibrium (EQ), Bory schema (BS), Spatial Orientation (SO) and Temporal Orientation (TO). We performed semi-structured interviews with parents of the subjects to check the activities that they perform at the time of leisure. The results obtained were analyzed by IM in each event and discussed by the descriptive analysis, mean and standard deviation between the CI and MI obtained as performance on tests. We used ANOVA (normal distribution) and Krusskal Wallis (non-normal distribution) to determine differences between groups, significance level p <0.05. The results show that most guys have the old general motor (OGM) appropriate to their chronological age (CA), normal average rating. However, the subjects of rural schools had the OGM ten months more than its CA, different; The subjects of rural schools perform more activities that require large body movements compared with others; In testing BS and TO subjects had difficulty because the old motor was rated below chronological age, but the subjects of rural schools had better results. We believe that the custom of the subjects of regional rural school influenced in making their results were superior.